Answer:
This is easy -- it's just a list of steps. At this level, the problems are pretty simple.
Let's just do one, then I'll write out the list of steps for you.
Find the inverse of f( x ) = -( 1 / 3 )x + 1
STEP 1: Stick a "y" in for the "f(x)" guy:
y = -( 1 / 3 )x + 1
STEP 2: Switch the x and y
( because every (x, y) has a (y, x) partner! ):
x = -( 1 / 3 )y + 1
STEP 3: Solve for y:
x = -( 1 / 3 )y + 1 ... multiply by 3 to ditch the fraction ... 3x = -y + 3 ... ditch the +3 ... subtract 3 from both sides ... 3x - 3 = -y ... multiply by -1 ... -3x + 3 = y ... y = -3x + 3
STEP 4: Stick in the inverse notation, f^( -1 )( x )
f^( -1 )( x ) = -3x + 3
Step-by-step explanation:
Answer:
f(x) = 401.19(1.08)x
Step-by-step explanation:
Answer:
m∠RST = 155°
m∠RSU = 102°
Step-by-step explanation:
m∠RST = m∠RSU + m∠UST
12x - 1 = 9x - 15 + 53
12x - 9x = 1- 15 + 53
3x = 39
x = 39/3
x = 13°
m∠RST = (12x -1)° = (12 * 13 - 1)° = (156 - 1 )° = 155°
m∠RSU = (9x -15)° = (9 * 13 - 15)° = ( 117 - 15)° = 102°
Not 100% sure but I think it’s b. hope this helps!
Answer:
Yes thank you
Step-by-step explanation: